Cytoreductive surgery for metastatic gastrointestinal stromal tumors followed by sunitinib compared to followed by imatinib-a multi-center cohort study. Issue 3 (March 2019) - Zhang, Xinhua; Zhou, Ye; Wu, Xin; Nie, Mingming; Zhang, Bo; Zhou, Yongjian; Sun, Lifeng; Liu, Zimin; Liu, Xiufeng; Kou, Youwei; Wang, Yongpeng; Zhang, Yefan; et al.
Abstract: Background: The progression-free survival (PFS) is not optimal when imatinib was recommended for treatment of gastrointestinal stromal tumor (GIST) undergoing surgery after tumor local or multifocal progression. Methods: We evaluate PFS of patients undergoing R0 resection or optimal cytoreductive surgery followed by sunitinib therapy compared with imatinib after tumor unifocal or multifocal progression. Results: From January 2006 to June 2017, ninety-seven patients from thirteen medical centers were enrolled. Fifty-six patients continued imatinib therapy and 41 patients switched sunitinib treatment directly after R0 resection or optimal cytoreductive surgery. The PFS of sunitinib group was longer than that of imatinib group (30.0 months vs 12.0 months, p = 0.009). In subgroup analysis, the PFS of the sunitinib and imatinib groups were 25.5 months and 12.0 months in patients with tumor multifocal progression ( p = 0.008), and 39.0 months and 13.0 months in patients with unifocal progression ( p = 0.156), respectively. PFS of postoperative sunitinib group was also superior to the total PFS of postoperative imatinib group (PFS of postoperative imatinib plus PFS of subsequent sunitinib therapy (30.0 months vs 21.0 months, p = 0.012). The overall survival in the sunitinib and imatinib groups were 37.0 months and 33.0 months, respectively (p = 0.794). Conclusions: Surgery followed by sunitinib in GIST patients with unifocal or multifocal progression on imatinib may improve PFS, compared with surgery followed by imatinib.